Human Rights Study on Remission for Corruption Convicts in Indonesia - Andi Muliyono; Andi Marlina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The moratorium on granting remissions for corruption convicts is a pro and contra in various circles in society. Government Regulation Number 99 of 2012 concerning Remission, some consider it a violation of human rights. But on the other hand, it is considered as one of the government's efforts to prevent corruption in Indonesia. The formulation of the problem in this study is how to provide remission for corruption convicts in Law no. 12 of 1995 concerning Corrections and what is the perspective of human rights (HAM) regarding the remission moratorium for corruption prisoners? The research uses empirical research methods. The conclusion in this study is that first remission is one of the rights for prisoners without exception for corruption convicts. This is regulated in the provisions of Article 14 paragraph (1) of Law Number 12 of 1995 concerning Corrections which mentions the rights of every prisoner, one of which is the right to get remission. Another thing is also regulated in Article 34 of Government Regulation Number 99 of 2012 concerning Terms and Procedures for the Implementation of the Rights of Correctional Inmates, which states that every prisoner has the right to get remission on condition that they must be of good behavior and have served a criminal period of more than 6 (six) months. . Second, the remission moratorium is a form of violation of legal rights for corrupt NAPIs. However, tightening the conditions for granting remission for corruption prisoners is the right and fair step for corruption prisoners and also for the community.